Exogenous Hemin alleviated cadmium stress in maize (Zea mays L.) by enhancing leaf photosynthesis, AsA-GSH cycle and polyamine metabolism - Piao, Lin; Wang, Yong; Liu, Xiaoming; Sun, Guangyan; Zhang, Shiyu; Yan, Junyao; Chen, Yang; Meng, Yao; Li, Ming; Gu, Wanrong (Frontiers in Plant Science, 2022)
Cadmium (Cd) stress is one of the principal abiotic stresses that inhibit maize growth. The research was to explore (hemin chloride) Hemin (100 μmol L-1) on photosynthesis, ascorbic acid (AsA)-glutathione (GSH) cycle system, and polyamine metabolism of maize under Cd stress (85 mg L-1) using nutrient solution hydroponics, with Tiannong 9 (Cd tolerant) and Fenghe 6 (Cd sensitive) as experimental materials. The results showed that Hemin can increase leaf photosynthetic pigment content and ameliorate the ratio of Chlorophyll a/chlorophyll b (Chla/Chlb) under Cd stress. The values of ribose 1, 5-diphosphate carboxylase/oxygenase (RuBPcase) and phosphoenolpyruvate carboxylase (PEPCase), and total xanthophyll cycle pool ((violoxanthin (V), antiflavin (A) and zeaxanthin (Z)) increased, which enhancing xanthophyll cycle (DEPS) de-epoxidation, and alleviating stomatal and non-stomatal limitation of leaf photosynthesis. Hemin significantly increased net photosynthetic rate (Pn), stomatal conductance (gs), transpiration rate (Tr), photochemical quenching coefficient (qP), PSII maximum photochemical efficiency (Fv/Fm), and electron transfer rate (ETR), which contributed to the improvement of the PSII photosynthetic system. Compared with Cd stress, Hemin can reduce thiobartolic acid reactant (TBARS) content, superoxide anion radical (O2-·) production rate, hydrogen peroxide (H2O2) accumulation, and the extent of electrolyte leakage (EL); decreased the level of malondialdehyde (MDA) content and increased the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT); slowed the decrease in dehydroascorbic acid reductase (DHAR) and monodehydroascorbate reductase (MDHAR) activity and the increase in glutathione reductase (GR) and ascorbate peroxidase (APX) activity in leaves; promoted the increase in AsA and GSH content, decreased dehydroascorbic acid (DHA) and oxidized glutathione (GSSG), and increased AsA/DHA and GSH/GSSG ratios under Cd stress. Hemin promoted the increase of conjugated and bound polyamine content, and the conversion process speed of free putrescine (Put) to free spermine (Spm) and spermidine (Spd) in maize; decreased polyamine oxidase (PAO) activity and increased diamine oxidase (DAO), arginine decarboxylase (ADC), ornithine decarboxylase (ODC) and S-adenosylmethionine decarboxylase (SAMDC) enzyme activities in leaves under Cd stress.